Managing virtual projects - Goncalves, Marcus (McGraw-Hill, 2005)
This book shows project leaders as well as company decision-makers how to reverse this costly trend, by providing the knowledge and tools they need to assess, control, and complete mission-critical projects from a distance. Written by Marcus Goncalves, a pioneer and innovator in the design and implementation of virtual project management (VPM) and electronic project management (ePM) systems, this timely guidebook explores the cultural, political, and operational challenges of VPM. At the same time, it provides project managers and members with a step-by-step primer for maximizing the advantages of VPM, while minimizing or even eliminating the disadvantages.